PENGGUNAAN ALIH KODE OLEH YOUTUBERS INDONESIA (SUATU ANALISIS SOSIOLINGUISTIK) - Sondakh, Pamela Gracia; Lasut, Theresia M.C; Manus, Jeane Angela (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTThis research is entitled â€œPenggunaan Alih Kode oleh Youtubers Indonesia : Suatu Analisis Sosiolinguistikâ€. This research aims to identify, analyze, and describe the codeswitching that appeared on youtube by Indonesian YouTubers and explain the reason for the phenomenon mentioned above. This research uses the descriptive method. The theories of Hoffman (1991) and Janet Holmes (2013) are used in this research. The data were collected from youtube videos in Indonesian â€“ English, and English-Indonesian from July â€“ December 2019 that was uploaded by more than 13 Indonesian YouTubers who were subscribed by the writer on youtube. The total number of code-switching is 90 data found from the conversation in videos and the title of content video. The result of this research shows that there are three types of code-switching on youtube, namely Inter-sentential switching with 39 data, Intra-sentential switching with 30 data, and Emblematic switching with 211 data. The result of this research also shows that there are six reasons which influence the use of code-switching on YouTubers, namely talking about a particular topic with 29 cases found, being emphatic about something (express solidarity) with 17 cases found, Interjection (inserting sentence fillers or sentence connectors) with 17 cases found, repetition used for clarification with 11 cases found, Intention of clarifying the speech content for interlocutor with 10 cases found, expressing group identity with 6 cases found. The dominant reasons which YouTubers used are talking about a particular topic with 29 casesÂ found.Key Words : Code Switching, Youtube, SociolinguisticÂ